Diagnoza logopedyczna noworodka i niemowlęcia - Gacka, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The issues of the speech-therapy early intervention were brought up in the article. An outline of the speech-therapy diagnosis of the newborn child and the infant was presented, and also the chosen tools were introduced in order to make the speechtherapy assessment of those babies.